Tree growth descriptors of main early-flowering almond Spanish varieties - Lovera M.; Arquero O.; Salguero A.; Pérez D.; García A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This work studies vegetative habits at the end of the first growing year of almond trees that were not pruned. The following 8 early-flowering Spanish varieties were studied: 'Asperilla', 'Blanquerna', 'Cartayera', 'Desmayo Largueta', 'Garrigues', 'Marcona', 'Peraleja' and 'Verd'; the Tunisian variety 'Achaak' was also studied. The parameters analysed were growth habit, trunk diameter, canopy height and width and the ratio between canopy height and width. Most varieties showed upright or spreading growth habit. No relevant differences on vigour were found among the studied varieties.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)